The Role of E-Learning in Supporting Adult Education - Andas, Netty Huzniati; Lek, Siri; Chai, Napat; Nurdiana, Nurdiana (Journal International Inspire Education Technology, 2025)
The growing demand for lifelong learning and professional development has increased the significance of e-learning in adult education. Traditional learning models often fail to accommodate the diverse needs of adult learners, who require flexible, accessible, and self-paced learning opportunities. E-learning has emerged as a critical tool in addressing these challenges by offering digital platforms that enhance knowledge acquisition, skill development, and career advancement. This study aims to examine the role of e-learning in supporting adult education by evaluating its impact on engagement, learning effectiveness, and accessibility. A mixed-methods approach was employed, combining survey data from adult learners, performance analysis from e-learning platforms, and instructor interviews. Findings indicate that e-learning enhances learner autonomy, facilitates personalized learning experiences, and improves accessibility for individuals with work or family commitments. Statistical analysis revealed a strong correlation between e-learning engagement and knowledge retention, while qualitative data emphasized the importance of interactive content and real-time feedback. The study concludes that e-learning serves as a valuable complement to traditional adult education, providing flexible and inclusive learning solutions. Future research should explore the long-term impact of e-learning on adult career progression and strategies to further enhance digital learning experiences.